An isocyanate-modified polyurethane cyanide gas barrier material and its preparation method
Patent Information
- Application Number
- CN202610873014.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2046-06-17
AI Technical Summary
内部孔隙会削弱基体的连续致密性,增加气体渗透通道,导致涂层的隔气阻水性能下降
[0047] 1. This invention introduces bicycloxazolidine as a latent crosslinking agent and combines it with chemically dehydrated inorganic fillers to regulate the curing reaction pathway of the material. Bicycloxazolidine undergoes a ring-opening reaction upon contact with water, generating active groups that can participate in the isocyanate curing reaction, thereby reducing the degree to which isocyanate groups directly react with water to generate carbon dioxide gas. This reaction pathway reduces the generation of pore defects during the crosslinking molding stage, helps the polyurethane matrix form a more continuous and dense phase structure, reduces the risk of gas diffusion channel formation, and thus supports the maintenance of the gas barrier, heat insulation, and auxiliary flame retardant properties of the cyanopolymer material. It also facilitates the corresponding heat insulation and expansion/charring effects of hollow glass microspheres and expandable graphite in the cured matrix.
Abstract
Description
Technical Field
[0001] This invention relates to the field of air-barrier materials technology, specifically to an isocyanate-modified polyurethane cyanopolymer air-barrier material and its preparation method. Background Technology
[0002] The base liquid of polyurethane cyanopolymer gas barrier materials is typically a prepolymer containing free isocyanate groups in its molecular structure. These isocyanate groups possess high chemical reactivity, forming the basis for the material's cross-linking and molding. To adapt to different engineering environment requirements, inorganic powders and other fillers are often incorporated into the prepolymer for blending modification during production to improve the material's mechanical properties or add specific functions. The resulting polymer cross-linked network after curing is relatively dense, reducing the penetration of gases and moisture; therefore, it can be used as a sealing and protective layer in the construction and corrosion protection fields.
[0003] In conventional applications, single-component polyurethane cyanopolymer systems are mostly applied using a direct coating method. After the material is exposed to air, the film-forming process mainly relies on the reaction of free isocyanate groups in the resin with ambient moisture, and the liquid components gradually solidify through subsequent crosslinking, ultimately forming a barrier layer with a continuous phase structure on the substrate surface.
[0004] Because isocyanate groups react with water to generate carbon dioxide gas, this curing method is prone to structural defects when filler modification is introduced. Inorganic powders typically contain trace amounts of moisture on their surfaces and within their pores that are difficult to remove completely through ordinary drying. When modified fillers are mixed into the resin, the introduced moisture promotes premature side reactions within the material. As the curing process progresses and the material viscosity increases, the generated carbon dioxide gas is not easily expelled in time and tends to remain in the cross-linked network, forming micropores. These internal pores weaken the continuity and density of the matrix, increase gas permeation channels, and reduce the coating's gas and water barrier properties. Furthermore, the aggregation of microbubbles at the powder-resin interface weakens the interfacial bonding between the inorganic and organic phases, making it difficult to fully realize the structural strength, thermal insulation, and flame retardant properties expected from filler modification.
[0005] Therefore, this invention proposes an isocyanate-modified polyurethane cyanide condensation barrier material and its preparation method to overcome the shortcomings of the prior art. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides an isocyanate-modified polyurethane cyanopolymer gas barrier material and its preparation method. When existing polyurethane polymers are used as gas barrier materials, a certain amount of active isocyanate groups are typically retained to meet the requirements of subsequent cross-linking molding. When these free isocyanate groups come into contact with a humid environment, or when the fillers mixed in the material contain residual moisture, these free groups easily react with water to generate carbon dioxide gas. If the carbon dioxide gas is not discharged in time, it can easily remain inside the molded structure and form micropores or defects, affecting the originally continuous and dense cyanopolymer solidified phase. The presence of internal pore defects increases the channels for gas diffusion within the material and also affects the integrity of the solidified structure, leading to varying degrees of degradation in the material's gas barrier, thermal insulation, and flame retardant properties.
[0007] To address the above problems, the present invention provides the following technical solution:
[0008] In a first aspect, the present invention provides an isocyanate-modified polyurethane cyanide-coated gas barrier material, which adopts the following technical solution:
[0009] Isocyanate prepolymer mixture: 140-150 parts;
[0010] Modified composite powder filler: 42.05–59.8 parts;
[0011] Molecular sieve activated powder: 3-5 parts;
[0012] Bicycloxazolidine: 8-12 parts.
[0013] By adopting the above technical solution, the bicyclic oxazolidine introduced into the material serves as a latent crosslinking agent. During the material curing stage, its oxazolidine ring structure can undergo ring-opening hydrolysis upon contact with water, generating intermediate products containing active amino and hydroxyl groups.
[0014] Based on this, the aforementioned active amino and hydroxyl groups can react with free isocyanate groups in the isocyanate prepolymer mixture and participate in cross-linking molding. This reaction pathway can reduce the degree to which moisture reacts directly with isocyanate groups to generate carbon dioxide gas, thereby reducing the probability of pore defects forming during the curing process and making it easier for the molded polymer to form a more continuous and dense cured phase.
[0015] For gas-barrier materials, a continuous and dense polymer matrix helps to extend the permeation paths of water vapor and oxygen, thereby improving their gas barrier properties. Furthermore, a cured state with fewer pore defects is beneficial for maintaining relatively uniform dispersion of modified composite powder fillers within the resin, reducing stress concentration or the formation of localized heat conduction channels, which is positive for maintaining the material's thermal insulation and flame-retardant effects. The addition of a small amount of molecular sieve activating powder can adsorb trace amounts of moisture introduced into the material during the early stages of preparation or storage, and together with bicyclooxazolidine, reduce the adverse effects of free water on the material's storage and curing process.
[0016] Preferably, the components comprise the following parts by weight: the isocyanate prepolymer mixture: 145 parts; the modified composite powder filler: 50.45 parts; the molecular sieve activated powder: 4 parts; and the bicyclooxazolidine: 10 parts.
[0017] By adopting the above technical solution, under this weight ratio, the isocyanate prepolymer mixture, modified composite powder filler, molecular sieve activated powder and bicyclooxazolidine have a good compatibility, which is beneficial to balance the material's reactivity, storage stability and density after curing.
[0018] Preferably, the modified composite powder filler is made from raw materials comprising the following parts by weight:
[0019] Expandable graphite: 30-40 parts;
[0020] Hollow glass microspheres: 10-15 parts;
[0021] Dopamine hydrochloride: 0.2–0.8 parts;
[0022] γ-glycidyl etheroxypropyltrimethoxysilane: 1.5–2.5 parts;
[0023] Zirconium acetylacetonate (IV): 0.05–0.30 parts;
[0024] Triethyl orthoformate: 0.3–1.2 parts.
[0025] By adopting the above technical solution, the added triethyl orthoformate can act as a chemical dehydrating agent, reacting with free water adsorbed on the surface of expandable graphite and hollow glass microspheres to generate low-molecular-weight byproducts such as alcohols and esters. During subsequent vacuum suction, some of these low-molecular-weight byproducts can be carried out, thereby reducing the adverse effects of water introduced by inorganic powders and dehydration byproducts on the isocyanate prepolymer mixture, and mitigating localized foaming caused by water participation in the reaction after the powder is mixed into the resin.
[0026] To improve the compatibility between inorganic powders and polyurethane resins, dopamine hydrochloride undergoes in-situ oxidative self-polymerization under a weakly alkaline environment, causing polydopamine to adhere to the powder surface and form a film. This film contains structures such as catechol and amino groups, which can provide active sites for subsequent silane treatment of the inorganic powder surface.
[0027] The methoxy groups in the added silane coupling agent can undergo hydrolysis, condensation, or surface bonding under the influence of trace amounts of moisture or surface-active groups on the powder surface, while the epoxy groups at the other end remain on the outer side of the powder surface. The coordination and reaction regulation effects of zirconium acetylacetonate (IV) at the interface enhance the bonding between the organic layer on the powder surface and the polyurethane macromolecular network. Through the above surface coating and interface regulation treatments, the bonding between the powder and the polymer matrix can be improved, reducing defects caused by insufficient interfacial bonding during the curing shrinkage stage, thereby helping to maintain the tensile strength and deformation adaptability of the coating film after molding.
[0028] Preferably, the isocyanate prepolymer mixture is made from raw materials comprising the following parts by weight:
[0029] Polyphenyl polymethylene polyisocyanate: 100 parts;
[0030] Polytetramethylene ether glycol: 40-50 parts.
[0031] By adopting the above technical solution, the selected polyphenyl polymethylene polyisocyanate backbone contains a benzene ring structure and has a high content of isocyanate groups, which can provide crosslinking reaction sites and a certain structural strength for the prepolymer. The polytetramethylene ether glycol participating in the prepolymerization reaction contains flexible ether bonds, which can introduce flexible segments into the prepolymerization reaction. The combination of the above rigid structure and flexible segments enables the cured material to maintain a certain structural strength while possessing deformation adaptability, reducing its risk of brittle cracking under alternating temperature differences or external forces.
[0032] Preferably, the expansion ratio of the expandable graphite is 150 mL / g to 250 mL / g; the hollow glass microspheres are closed-cell hollow glass microspheres with an average particle size of 20 μm to 60 μm; the molecular sieve activation powder is type 3A molecular sieve activation powder with an effective pore size of 0.3 nm; the average functionality of the polyphenyl polymethylene polyisocyanate is 2.6 to 2.8; and the number average molecular weight of the polytetramethylene ether glycol is 1000 g / mol to 2000 g / mol.
[0033] By employing the above technical solutions, molecular sieve activated powder with an effective pore size of 0.3 nm can adsorb trace amounts of free water in the material and reduce the adsorption impact on larger molecular components such as bicyclooxazolidine. Closed-cell hollow glass microspheres, with their enclosed cavities, dispersed in the polyurethane cured phase, can reduce direct heat transfer in the solid phase, thus improving the material's thermal insulation performance. Expandable graphite expands upon heating, forming an expanded carbon layer that acts as a barrier on the material surface, slowing the transfer of oxygen and heat into the material, thereby providing auxiliary flame retardancy. Furthermore, by matching the functionality range of the polyisocyanate with the molecular weight range of the polyether glycol, the cross-linking structure of the prepolymer can be adjusted, maintaining a reasonable balance between the rheological properties during coating and the mechanical properties after curing.
[0034] Secondly, the present invention provides a method for preparing an isocyanate-modified polyurethane cyanide-based gas barrier material, employing the following technical solution:
[0035] A method for preparing an isocyanate-modified polyurethane cyanide-based gas barrier material includes the following steps:
[0036] S1. Add the modified composite powder filler, isocyanate prepolymer mixture and molecular sieve activated powder into a disperser and disperse at 600 r / min to 1000 r / min for 15 to 25 minutes to obtain the composite initial mixture slurry.
[0037] S2. Control the temperature of the composite initial mixture to drop to 15℃~20℃, turn on the vacuum pump to evacuate to -0.095MPa~-0.098MPa, disperse at 2000r / min~3000r / min under constant temperature and vacuum conditions, inject bicycloxazolidine into the composite initial mixture, maintain dispersion and continue stirring for 20~40 minutes to obtain a degassing and sealing mixture; then fill the degassing and sealing mixture with dry nitrogen to release the vacuum, and package and seal to obtain the isocyanate modified polyurethane cyanopolymer gas barrier material.
[0038] By employing the above technical solution, the preliminary dispersion treatment ensures thorough mixing of the modified composite powder filler, isocyanate prepolymer mixture, and molecular sieve activated powder. After the initial composite slurry is formed, controlling the material temperature at 15℃~20℃ reduces the degree of premature reaction between isocyanate groups and latent crosslinking agents in the initial mixing stage. Injecting bicycloxazolane at a lower temperature helps reduce the rapid viscosity increase caused by the addition of crosslinking aids, thereby improving the rheological stability of the single-component material during storage. Simultaneously introducing high vacuum and high-speed dispersion conditions during cooling allows microbubbles introduced by the initial stirring to be expelled under negative pressure, and ensures uniform dispersion of bicycloxazolane in the slurry. At the end of dispersion, dry nitrogen is introduced to release the vacuum and reduce the material's contact with external moisture, thus helping to maintain the material's latent stability before opening and use.
[0039] Preferably, prior to step S1, the preparation steps of the isocyanate prepolymer mixture include:
[0040] Polyphenyl polymethylene polyisocyanate was added to a nitrogen-protected reactor, and the temperature was raised to 65°C to 70°C with stirring. Polytetramethylene ether glycol was added dropwise to the reactor at a uniform rate over 30 to 60 minutes. After the addition was completed, the temperature of the reactor was raised to 80°C to 85°C, and the reaction was stirred continuously for 2 to 3 hours. The mixture was then cooled to obtain the isocyanate prepolymer mixture.
[0041] By employing the above technical solution, the addition reaction between isocyanate groups and hydroxyl groups during the prepolymer synthesis process releases heat. Uniformly adding polytetramethylene ether glycol (PTG) makes the exothermic reaction process more gradual, reducing the risk of side reactions caused by excessively rapid local temperature rise. After the addition is complete, increasing the temperature and extending the stirring time helps to improve the degree of reaction between the hydroxyl and isocyanate groups in the PTG, reducing the impact of unreacted hydroxyl components on the subsequent curing stability.
[0042] Preferably, before step S1, the preparation steps of the modified composite powder filler include: (1) adding expandable graphite and hollow glass microspheres to a mixed solvent prepared with anhydrous ethanol and water and stirring to obtain a suspension, adding tris(hydroxymethyl)aminomethane aqueous solution to adjust the pH of the suspension to 8.0-8.5; adding dopamine hydrochloride and controlling the temperature at 25℃-40℃ and stirring continuously for 1-3 hours to obtain a primary activated mixture; filtering the primary activated mixture to separate and retain solid matter to obtain a primary filter cake, washing the primary filter cake with anhydrous ethanol, and vacuum drying at 100℃-120℃ until the moisture content is not greater than 0.05% to obtain a pre-activated filler; (2) transferring the pre-activated filler into a mixing tank and spraying γ-glucopyranosyl chloride into the mixture. Glyceryl etheroxypropyltrimethoxysilane was heated and stirred at 80℃~90℃ for 1~1.5 hours to obtain silane-treated filler; then cooled to 60℃~70℃ and under nitrogen protection, zirconium acetylacetonate (IV) was added and stirred for 20~40 minutes to obtain pre-regulated modified filler; (3) Triethyl orthoformate was sprayed into the mixing tank and stirred with the pre-regulated modified filler at 60℃~70℃ for 15~20 minutes to obtain dehydrated reaction material; then the vacuum degree was evacuated to -0.090MPa~-0.098MPa and the vacuum state was maintained at 60℃~70℃ for 30~45 minutes. After the evacuation was completed, dry nitrogen was introduced to release the vacuum and the temperature was lowered to obtain modified composite powder filler.
[0043] By employing the above technical solution, the weakly alkaline liquid phase conditions in the powder activation treatment provide a reaction environment for the oxidative self-polymerization of dopamine hydrochloride. Under stirring, polydopamine can adhere to the surface of expandable graphite and hollow glass microspheres. After pressure filtration and washing, the powder is vacuum dried to reduce the moisture content on the powder surface and in the pores, thus mitigating the impact of powder mixing on the polyurethane curing process.
[0044] In the powder mixing process, the degree of condensation grafting reaction between the silane coupling agent and the polydopamine coating layer is enhanced under heating conditions. After the grafting operation is completed, the material temperature is reduced, and zirconium acetylacetonate (IV) is added under nitrogen protection, which is beneficial to the distribution of zirconium acetylacetonate (IV) on the powder surface and plays an interfacial regulation role.
[0045] During the dehydration process, the triethyl orthoformate introduced by spraying reacts with trace amounts of moisture on the powder surface that are difficult to remove completely by physical heating. After closed stirring, negative pressure suction is applied, and low-molecular-weight byproducts such as alcohols produced in the reaction can be carried out under negative pressure. This combination of chemical dehydration and negative pressure suction reduces the moisture content of the filler and the residue of low-molecular-weight byproducts, thereby helping to improve the accelerated storage stability of single-component polyurethane materials.
[0046] This invention provides an isocyanate-modified polyurethane cyanide-coated gas barrier material and its preparation method. It has the following beneficial effects:
[0047] 1. This invention introduces bicycloxazolidine as a latent crosslinking agent and combines it with chemically dehydrated inorganic fillers to regulate the curing reaction pathway of the material. Bicycloxazolidine undergoes a ring-opening reaction upon contact with water, generating active groups that can participate in the isocyanate curing reaction, thereby reducing the degree to which isocyanate groups directly react with water to generate carbon dioxide gas. This reaction pathway reduces the generation of pore defects during the crosslinking molding stage, helps the polyurethane matrix form a more continuous and dense phase structure, reduces the risk of gas diffusion channel formation, and thus supports the maintenance of the gas barrier, heat insulation, and auxiliary flame retardant properties of the cyanopolymer material. It also facilitates the corresponding heat insulation and expansion / charring effects of hollow glass microspheres and expandable graphite in the cured matrix.
[0048] 2. This invention utilizes dopamine to self-polymerize and coat the surface of inorganic powder, providing attachment sites for silane coupling agent grafting, and employs zirconium acetylacetonate (IV) to regulate the interfacial reaction. After the powder undergoes this treatment, when mixed into a prepolymer liquid phase containing free isocyanate groups, its epitaxial active ends facilitate interfacial bonding with the polyurethane macromolecular network. This powder surface modification improves the interfacial bonding between the inorganic and organic phases, reducing interfacial debonding under stress, thereby helping to maintain the tensile strength and strain adaptability of the cyanide-coated gas barrier material after curing.
[0049] 3. This invention controls the temperature and degassing conditions during the initial mixing of the active components by cooling the composite initial slurry and dispersing and injecting the crosslinking aid under high vacuum. The low-temperature environment helps reduce the early reaction between isocyanate groups and latent crosslinking agents within the prepolymer, while negative pressure stirring helps remove air bubbles introduced during the initial mixing process. This combination of cooling and degassing during the sealing process reduces premature reactions and residual air bubbles before final packaging, lowering the risk of abnormal viscosity increases in the packaged product. This, in turn, helps the single-component cyanopolymer gas-barrier material maintain a relatively stable rheological state and latent stability during its storage period. Detailed Implementation
[0050] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0051] The main raw materials and reagents used in the following preparation examples, embodiments and comparative examples are as follows. Raw materials or reagents not specifically mentioned are all commercially available products, and the reagents are analytical grade or higher grade products.
[0052] Polyphenyl polymethylene polyisocyanate, CAS No. 9016-87-9, with an average functionality of 2.6 to 2.8. Polytetramethylene ether glycol, CAS No. 25190-06-1, with a number-average molecular weight of 1000 g / mol to 2000 g / mol. Expandable graphite, with an expansion ratio of 150 mL / g to 250 mL / g. Hollow glass microspheres, which are closed-cell, with an average particle size of 20 μm to 60 μm. Dopamine hydrochloride, CAS No. 62-31-7. Tris(hydroxymethyl)aminomethane, CAS No. 77-86-1. γ-glycidyl etheroxypropyltrimethoxysilane, CAS No. 2530-83-8. Zirconium acetylacetonate (IV), CAS No. 17501-44-9. Triethyl orthoformate, CAS No. 122-51-0. Molecular sieve activated powder, type 3A, CAS number 1318-02-1, effective pore size 0.3nm. Bicycloxazolidine, CAS number 56709-13-8.
[0053] In the following preparation examples, embodiments, and comparative examples, "parts" refers to parts by weight; the moisture content in the following preparation examples was determined by the Karl Fischer method.
[0054] Preparation Example 1:
[0055] This preparation example provides a method for preparing modified composite powder fillers, including the following steps:
[0056] (1) Add 35 parts of expandable graphite and 12 parts of hollow glass microspheres to the reaction vessel, add 110 parts of a mixed solvent prepared by anhydrous ethanol and water in a mass ratio of 1:1, stir at a speed of 400 r / min, add tris(hydroxymethyl)aminomethane aqueous solution dropwise until the pH value of the suspension is 8.2, add 0.5 parts of dopamine hydrochloride, control the temperature at 32℃ and continue stirring for 2 hours to obtain the primary activation mixture;
[0057] The primary activated mixture is subjected to pressure filtration to separate the solid and liquid phases, and the solid material is retained to obtain the primary filter cake. The primary filter cake is washed three times with anhydrous ethanol to obtain the washed filter cake. The washed filter cake is placed in a vacuum drying oven and dried at 110℃ for more than 2 hours until the moisture content is ≤0.05%, thus obtaining the pre-activated packing material.
[0058] (2) The pre-activated filler was transferred into a closed powder mixing tank, and 2.0 parts of γ-glycidyl ether oxypropyltrimethoxysilane were sprayed in. The mixture was stirred at a speed of 1000 r / min, and the material temperature was controlled at 85℃. The stirring was maintained for 1.2 hours to obtain silane-treated filler. Then the material temperature was reduced to 65℃, and 0.15 parts of zirconium acetylacetonate (IV) were added under nitrogen protection. The mixture was kept in a closed state and stirred at a speed of 1000 r / min for 30 minutes to obtain pre-regulated modified filler.
[0059] (3) Control the temperature of the pre-modified filler to 65℃, spray 0.8 parts of triethyl orthoformate into the mixing tank, stir at 1000r / min for 18 minutes in a closed state to obtain the dehydrated reaction material; then turn on the vacuum pump connected to the mixing tank, draw the vacuum to -0.095MPa, maintain the vacuum state at 65℃ for 38 minutes, after the suction is completed, fill with dry nitrogen to release the vacuum, and lower the material temperature to 25℃ to obtain the modified composite powder filler.
[0060] Preparation Example 2:
[0061] This preparation example provides a method for preparing modified composite powder fillers, including the following steps:
[0062] (1) Add 30 parts of expandable graphite and 10 parts of hollow glass microspheres to a reaction vessel, add 100 parts of a mixed solvent prepared by anhydrous ethanol and water in a mass ratio of 1:1, stir at a speed of 300 r / min, add tris(hydroxymethyl)aminomethane aqueous solution dropwise until the pH value of the suspension is 8.0, add 0.2 parts of dopamine hydrochloride, control the temperature at 25℃ and stir continuously for 1 hour to obtain a primary activation mixture; perform pressure filtration to separate the solid and liquid phases of the primary activation mixture, retain the solid material to obtain the primary filter cake, wash the primary filter cake 3 times with anhydrous ethanol to obtain a washed filter cake; place the washed filter cake in a vacuum drying oven, control the temperature at 100℃ and dry for more than 2 hours until the moisture content is ≤0.05% to obtain the pre-activated packing.
[0063] (2) The pre-activated filler was transferred into a closed powder mixing tank, and 1.5 parts of γ-glycidyl ether oxypropyltrimethoxysilane were sprayed in. The mixture was stirred at a speed of 800 r / min, and the material temperature was controlled at 80℃ and stirred for 1 hour to obtain silane-treated filler. Then the material temperature was reduced to 60℃, and 0.05 parts of zirconium acetylacetonate (IV) were added under nitrogen protection. The mixture was kept in a closed state and stirred at a speed of 800 r / min for 20 minutes to obtain pre-regulated modified filler.
[0064] (3) Control the temperature of the pre-modified filler to 60°C, spray 0.3 parts of triethyl orthoformate into the mixing tank, stir at 800 r / min for 15 minutes in a closed state to obtain the dehydrated reaction material; then turn on the vacuum pump connected to the mixing tank to draw the vacuum to -0.090 MPa, maintain the vacuum state at 60°C for 30 minutes, after the suction is completed, fill with dry nitrogen to release the vacuum, and lower the material temperature to 25°C to obtain the modified composite powder filler.
[0065] Preparation Example 3:
[0066] This preparation example provides a method for preparing modified composite powder fillers, including the following steps:
[0067] (1) Add 40 parts of expandable graphite and 15 parts of hollow glass microspheres to a reactor, add 120 parts of a mixed solvent prepared by anhydrous ethanol and water in a mass ratio of 1:1, stir at a speed of 500 r / min, add tris(hydroxymethyl)aminomethane aqueous solution dropwise until the pH value of the suspension is 8.5, add 0.8 parts of dopamine hydrochloride, control the temperature at 40℃ and stir continuously for 3 hours to obtain a primary activation mixture; perform pressure filtration to separate the solid and liquid phases of the primary activation mixture, retain the solid material to obtain the primary filter cake, wash the primary filter cake 3 times with anhydrous ethanol to obtain a washed filter cake; place the washed filter cake in a vacuum drying oven, control the temperature at 120℃ and dry for more than 2 hours until the moisture content is ≤0.05% to obtain the pre-activated packing.
[0068] (2) Transfer the pre-activated filler into a closed powder mixing tank, spray in 2.5 parts of γ-glycidyl ether oxypropyltrimethoxysilane, stir at a speed of 1200 r / min, control the material temperature at 90℃ and keep stirring for 1.5 hours to obtain silane-treated filler.
[0069] The material temperature was then lowered to 70°C, and 0.30 parts of zirconium acetylacetonate (IV) were added under nitrogen protection. The mixture was kept sealed and stirred for 40 minutes at 1200 r / min to obtain the pre-regulated modified filler.
[0070] (3) Control the temperature of the pre-modified filler to 70°C, spray 1.2 parts of triethyl orthoformate into the mixing tank, stir at 1200 r / min for 20 minutes in a closed state to obtain the dehydrated reaction material; then turn on the vacuum pump connected to the mixing tank, draw the vacuum to -0.098 MPa, maintain the vacuum state at 70°C for 45 minutes, after the suction is completed, fill with dry nitrogen to release the vacuum, and lower the material temperature to 25°C to obtain the modified composite powder filler.
[0071] Preparation Example 4:
[0072] This preparation example provides a method for preparing an isocyanate prepolymer mixture, comprising the following steps:
[0073] 100 parts of polyphenyl polymethylene polyisocyanate were added to a nitrogen-protected reactor and heated to 68°C. The mixture was stirred at 250 r / min and 45 parts of polytetramethylene ether glycol with a number average molecular weight of 1500 g / mol were added dropwise over 45 minutes. After the addition was complete, the reactor temperature was raised to 82°C and the mixture was stirred continuously at 250 r / min for 2.5 hours. The mixture was then cooled to 25°C to obtain a mixture of isocyanate prepolymers containing free isocyanate groups.
[0074] Preparation Example 5:
[0075] This preparation example provides a method for preparing an isocyanate prepolymer mixture, comprising the following steps:
[0076] 100 parts of polyphenyl polymethylene polyisocyanate were added to a nitrogen-protected reactor and heated to 65°C. The mixture was stirred at 200 r / min and 40 parts of polytetramethylene ether glycol with a number average molecular weight of 1000 g / mol were added dropwise over 30 minutes. After the addition was complete, the reactor temperature was raised to 80°C and the mixture was stirred continuously at 200 r / min for 2 hours. The mixture was then cooled to 25°C to obtain a mixture of isocyanate prepolymers containing free isocyanate groups.
[0077] Preparation Example 6:
[0078] This preparation example provides a method for preparing an isocyanate prepolymer mixture, comprising the following steps:
[0079] 100 parts of polyphenyl polymethylene polyisocyanate were added to a nitrogen-protected reactor and heated to 70°C. The mixture was stirred at 300 r / min and 50 parts of polytetramethylene ether glycol with a number average molecular weight of 2000 g / mol were added dropwise over 60 minutes. After the addition was complete, the reactor temperature was raised to 85°C and the mixture was stirred continuously at 300 r / min for 3 hours. The mixture was then cooled to 25°C to obtain a mixture of isocyanate prepolymers containing free isocyanate groups.
[0080] Example 1:
[0081] This embodiment provides a method for preparing an isocyanate-modified polyurethane cyanide-based gas barrier material, including the following steps:
[0082] S1. 50.45 parts of the modified composite powder filler prepared in Preparation Example 1, 145 parts of the isocyanate prepolymer mixture prepared in Preparation Example 4, and 4 parts of molecular sieve activated powder were added to a disperser with cooling and vacuum functions and dispersed at 800 r / min for 20 minutes to obtain a composite initial mixture slurry.
[0083] S2. Control the temperature of the composite initial mixture to drop to 18℃, turn on the vacuum pump to -0.096MPa, disperse at 2500r / min under the condition of 18℃, inject 10 parts of bicycloxazolidine into the composite initial mixture, and continue stirring for 30 minutes while maintaining the conditions of -0.096MPa and 18℃ to obtain a degassed and sealed mixture; purge the degassed and sealed mixture with dry nitrogen to release the vacuum, and dispense and seal to obtain isocyanate modified polyurethane cyanopolymer gas barrier material.
[0084] Example 2:
[0085] This embodiment provides a method for preparing an isocyanate-modified polyurethane cyanide-based gas barrier material, including the following steps:
[0086] S1. 42.05 parts of the modified composite powder filler prepared in Preparation Example 2, 140 parts of the isocyanate prepolymer mixture prepared in Preparation Example 5, and 3 parts of molecular sieve activated powder were added to a disperser with cooling and vacuum functions and dispersed at 600 r / min for 15 minutes to obtain a composite initial mixture slurry.
[0087] S2. Control the temperature of the composite initial mixture to drop to 15℃, turn on the vacuum pump to -0.095MPa, disperse at 2000r / min under the condition of 15℃, inject 8 parts of bicycloxazolidine into the composite initial mixture, and continue stirring for 20 minutes while maintaining the conditions of -0.095MPa and 15℃ to obtain a degassing and sealing mixture; purge the degassing and sealing mixture with dry nitrogen to release the vacuum, and dispense and seal to obtain isocyanate modified polyurethane cyanopolymer gas barrier material.
[0088] Example 3:
[0089] This embodiment provides a method for preparing an isocyanate-modified polyurethane cyanide-based gas barrier material, including the following steps:
[0090] S1. 59.8 parts of the modified composite powder filler prepared in Preparation Example 3, 150 parts of the isocyanate prepolymer mixture prepared in Preparation Example 6, and 5 parts of molecular sieve activated powder were added to a disperser with cooling and vacuum functions and dispersed at 1000 r / min for 25 minutes to obtain a composite initial mixture slurry.
[0091] S2. Control the temperature of the composite initial mixture to drop to 20℃, turn on the vacuum pump to -0.098MPa, disperse at 3000r / min under 20℃ conditions, inject 12 parts of bicycloxazolidine into the composite initial mixture, maintain -0.098MPa and 20℃ conditions and continue stirring for 40 minutes to obtain a degassing and sealing mixture; purge the degassing and sealing mixture with dry nitrogen to release the vacuum, and dispense and seal to obtain isocyanate modified polyurethane cyanopolymer gas barrier material.
[0092] Comparative Example 1:
[0093] Compared with Example 1, the difference is that dopamine hydrochloride was not added in (1) of Preparation Example 1, but the rest are the same.
[0094] Comparative Example 2:
[0095] The difference from Example 1 is that zirconium acetylacetonate (IV) was not added in (2) of Preparation Example 1, but all other aspects are the same.
[0096] Comparative Example 3:
[0097] Compared with Example 1, the difference is that the pre-regulated modified filler was prepared according to (1) and (2) of Preparation Example 1, and the (3) treatment in Preparation Example 1 was not performed; and in S1 of Example 1, the modified composite powder filler prepared in Preparation Example 1 was replaced with the pre-regulated modified filler, and 0.8 parts of triethyl orthoformate were added together with the pre-regulated modified filler, the isocyanate prepolymer mixture and the molecular sieve activated powder into the disperser, and the rest were the same.
[0098] Comparative Example 4:
[0099] Compared with Example 1, the difference is that in S2 of Example 1, the temperature of the composite primary slurry is not reduced to 18°C, but the temperature of the composite primary slurry is controlled at 35°C, the vacuum pump is turned on to -0.096MPa, and the dispersion is carried out at 2500r / min under the condition of 35°C. The rest are the same.
[0100] Comparative Example 5:
[0101] The difference from Example 1 is that bicycloxazolidine is not injected in S2 of Example 1, but all other steps are the same.
[0102] Test Example 1:
[0103] Experimental steps:
[0104] (1) The isocyanate-modified polyurethane cyanide barrier materials prepared in Examples 1 to 3, Comparative Example 3 and Comparative Example 4 were used as test objects. One sample with a mass of 2.5g was weighed independently from each test object for the determination of the mass fraction of free -NCO groups, and four samples with a mass of 200g were weighed independently for the determination of accelerated storage viscosity.
[0105] (2) Place 2.5g samples of each of the aforementioned test objects into conical flasks, add 25mL of anhydrous toluene to dissolve the resin components and form a uniformly dispersed system; accurately add 25mL of di-n-butylamine-toluene standard solution using a pipette, and shake the mixture under closed conditions for 15 minutes; add 100mL of isopropanol to terminate the reaction, and add bromocresol green-methyl red mixed indicator; titrate with 0.5mol / L hydrochloric acid standard titration solution, and determine the titration endpoint by potentiometric titration. At the same time, perform a blank test without adding the test objects, that is, mix only 25mL of anhydrous toluene with 25mL of di-n-butylamine-toluene standard solution, shake under closed conditions for 15 minutes, add 100mL of isopropanol, add bromocresol green-methyl red mixed indicator, titrate with 0.5mol / L hydrochloric acid standard titration solution, and determine the titration endpoint by potentiometric titration. The initial free NCO group mass fraction is calculated using the formula: Initial free NCO group mass fraction = (volume of standard hydrochloric acid solution consumed in blank test - volume of standard hydrochloric acid solution consumed in test object) × concentration of standard hydrochloric acid solution × 4.202 ÷ mass of test sample.
[0106] (3) Four 200g samples from each of the aforementioned test objects were placed into 250mL tinplate containers, filled with nitrogen and sealed. These four independently sealed tinplate containers were then placed in a constant temperature aging test chamber set at 50℃ for accelerated storage. On day 0, the sample from the first tinplate container was cooled to 25℃ and kept at a constant temperature. The initial viscosity of the sample was then tested using a rotational viscometer at a speed of 60r / min. On days 7, 14, and 28, the second, third, and fourth tinplate containers were independently removed, cooled to 25℃, and their viscosities after aging at 50℃ for 7 days, 14 days, and 28 days, respectively, were tested. Samples with viscosities exceeding the range or unable to flow were recorded as being in a gel state.
[0107] The experimental results are shown in Table 1:
[0108] Table 1: Results of Reaction Control and Storage Stability Tests for Single-Group Separator Gas Materials
[0109] object Initial free NCO mass fraction (%) Initial viscosity (mPa·s) Viscosity (mPa·s) after aging at 50℃ for 7 days Viscosity (mPa·s) after aging at 50℃ for 14 days Viscosity (mPa·s) after aging at 50℃ for 28 days Example 1 13.62 8540 8920 9350 9810 Example 2 14.05 8310 8670 9120 9630 Example 3 12.88 8820 9150 9680 10240 Comparative Example 3 10.74 10320 16650 24180 33860 Comparative Example 4 12.91 11250 45800 gel gel
[0110] Test conclusion:
[0111] According to the data in Table 1, comparing the data of the comparative examples and Comparative Example 3, the initial free -NCO mass fraction of Examples 1 to 3 remained between 12.88% and 14.05%, while the initial free -NCO mass fraction of Comparative Example 3 was 10.74%. Comparative Example 3 omitted the powder dehydration treatment and directly added triethyl orthoformate to the composite initial mixture. The residual moisture in the powder and the alcohol byproducts generated from the dehydration reaction of triethyl orthoformate could consume some of the -NCO groups, resulting in a lower initial free -NCO mass fraction in Comparative Example 3 compared to Examples 1 to 3. Simultaneously, the viscosity increase of Comparative Example 3 during accelerated aging at 50°C was greater than that of Examples 1 to 3, indicating that pre-treatment of the powder with vacuuming is beneficial in reducing the impact of residual moisture and dehydration byproducts in the composite initial mixture on storage stability.
[0112] Comparing the data from the examples and Comparative Example 4, it can be seen that in Comparative Example 4, when bicycloxazolane was injected into the composite initial slurry at 35°C, the initial viscosity reached 11250 mPa·s. After accelerated aging at 50°C for 7 days, the viscosity increased to 45800 mPa·s, and gelation occurred after 14 days. This result indicates that a higher sealing temperature accelerates the reaction process between the active components in the material, making the material more prone to rapid viscosity increases during accelerated storage. In Examples 1 to 3, by controlling the temperature of the composite initial slurry between 15°C and 20°C before injecting bicycloxazolane, the viscosity increase of the samples after accelerated aging at 50°C for 28 days was slower, with viscosities of 9810 mPa·s, 9630 mPa·s, and 10240 mPa·s, respectively. This indicates that low-temperature vacuum sealing conditions are beneficial for maintaining the storage stability of single-unit separator gas materials.
[0113] Test Example 2:
[0114] Experimental steps:
[0115] (1) The isocyanate-modified polyurethane cyanopolymer gas barrier materials prepared in Examples 1 to 3, Comparative Examples 1, 2 and 5 were uniformly coated on the surface of a polytetrafluoroethylene template. The ambient temperature was controlled at 25±2℃ and the relative humidity at 50±5%, and the material was allowed to stand for curing for 7 days. Then the cured coating was peeled off from the template, and 6 circular samples with a thickness of 1.5±0.1mm were cut from each test object. Three of them were used for water vapor transmission rate testing and the other three were used for oxygen transmission rate testing.
[0116] (2) The sample is sealed and fixed in a permeation cup containing desiccant and placed in a constant temperature and humidity environment with a test temperature of 38℃ and a relative humidity difference of 90% between the test environment and the permeation cup. Water vapor passes through the sample into the permeation cup and is absorbed by the desiccant. The mass increase of the permeation cup over time is measured, and the mass of water vapor permeated per unit area of each sample in 24 hours is measured. Three samples are tested in parallel for each test object, and the arithmetic mean is taken to calculate the water vapor transmission rate of the test object.
[0117] (3) Fix the sample between the high-pressure side and the low-pressure side chamber of the gas permeability tester, use high-purity oxygen as the test gas, set the pressure on the high-pressure side to 0.1 MPa, keep the low-pressure side in a vacuum state, and the test temperature to 23℃. Use a pressure sensor to monitor the pressure change on the low-pressure side, record the volume of gas permeating into the low-pressure side per unit area per unit time for each sample, test 3 samples in parallel for each test object, take the arithmetic mean, and calculate the oxygen permeability of the test object.
[0118] The experimental results are shown in Table 2:
[0119] Table 2: Test results of water vapor and gas barrier properties of cured coatings
[0120] object <![CDATA[Water vapor transmission rate (g / (m 2 ·24h))]]> <![CDATA[Oxygen transmission rate (cm 3 / (m 2 ·24h·0.1MPa))]]> Example 1 1.25 5.38 Example 2 1.34 5.12 Example 3 1.18 5.61 Comparative Example 1 6.86 24.31 Comparative Example 2 4.27 15.86 Comparative Example 5 10.94 38.42
[0121] Test conclusion:
[0122] According to the data in Table 2, the water vapor transmission rate of Examples 1 to 3 is 1.18 g / (m²). 2 • 24h) to 1.34g / (m 2 Oxygen permeability was 5.12 cm⁻¹ between 24 hours and 24 hours. 3 / (m 2 •24h•0.1MPa) to 5.61cm 3 / (m 2 It exhibits a low permeability level between 24h and 0.1MPa.
[0123] As can be seen from the data of the comparative example and Comparative Example 1, the water vapor transmission rate and oxygen transmission rate of Comparative Example 1 increased to 6.86 g / (m³). 2 ·24h) and 24.31cm 3 / (m 2 (24h, 0.1MPa). Comparative Example 1 did not undergo dopamine pre-activation, resulting in fewer active sites on the surface of expandable graphite and hollow glass microspheres available for silane coupling agent action, leading to lower interfacial bonding strength between the inorganic filler and the resin matrix. Under the influence of coating curing shrinkage and external stress, interfacial defects easily form at the weak connections, thereby increasing gas diffusion channels and reducing the barrier properties of the coating.
[0124] Comparing the data of the comparative example and Comparative Example 2, it can be seen that the water vapor transmission rate and oxygen transmission rate of Comparative Example 2 increased to 4.27 g / (m³). 2 ·24h) and 15.86cm 3 / (m 2 •24h•0.1MPa). Comparative Example 2 did not add zirconium acetylacetonate (IV). Although the surface of the inorganic filler was treated with epoxy silane, the lack of the regulatory effect of zirconium acetylacetonate (IV) on the interfacial reaction resulted in a decrease in the density of the interfacial bonding layer between the filler surface and the polyurethane macromolecules, thereby making the water vapor permeability and oxygen permeability higher than those of Examples 1 to 3.
[0125] Comparing the data of the comparative examples with those of Comparative Example 5, it can be seen that the various permeability indicators of Comparative Example 5 increased significantly, with its water vapor transmission rate reaching 10.94 g / (m²). 2 (24h), oxygen permeability reached 38.42 cm³. 3 / (m 2(24h, 0.1MPa). Comparative Example 5, which removed the bicycloxazolidine, relied primarily on the reaction of free isocyanate groups with moisture in the air for curing. This curing pathway is more prone to carbon dioxide gas generation, making the coating more susceptible to pore defects during cross-linking. These pore defects reduce the continuity of the polymer film, increasing the permeability of water and oxygen molecules.
[0126] Examples 1 to 3 enhanced the interfacial bonding between the inorganic filler and the organic resin phase through dopamine activation, silane coupling, and the interfacial regulation effect of zirconium acetylacetonate (IV). Furthermore, the participation of bicyclooxazolidine in the curing reaction reduced the risk of pore defects caused by carbon dioxide gas, thus maintaining good continuity of the cured coating and achieving lower water vapor transmission rate and oxygen transmission rate.
[0127] Test Example 3:
[0128] Experimental steps:
[0129] (1) The isocyanate-modified polyurethane cyanopolymer gas barrier materials prepared in Examples 1 to 3, Comparative Example 1 and Comparative Example 2 were uniformly coated onto the surface of a polytetrafluoroethylene template. The ambient temperature was controlled at 25±2℃ and the relative humidity at 50±5%, and the material was allowed to cure for 7 days. Subsequently, the cured coating was peeled off from the template, and five dumbbell-shaped samples with a total length of 115mm, an end width of 25mm, a narrow parallel section length of 33mm, a narrow parallel section width of 6mm, and a thickness of 1.5±0.1mm were cut from each test object for tensile strength and elongation at break tests.
[0130] (2) Install the cut sample between the upper and lower clamps of the universal testing machine, set the tensile speed to 500 mm / min, start the testing machine to perform axial tension on the sample, record the initial cross-sectional area and initial gauge length of the sample, record the maximum tensile force and gauge length at tensile fracture. Divide the maximum tensile force by the initial cross-sectional area of the sample to obtain the tensile strength of each sample, divide the difference between the gauge length at tensile fracture and the initial gauge length by the initial gauge length and multiply by 100% to obtain the elongation at break of each sample, test 5 samples in parallel for each test object, take the arithmetic mean, and calculate the tensile strength and elongation at break of the test object.
[0131] The experimental results are shown in Table 3:
[0132] Table 3: Test results of mechanical properties of cured coating film
[0133] object Tensile strength (MPa) Elongation at break (%) Example 1 5.34 421.5 Example 2 5.72 482.3 Example 3 5.18 453.8 Comparative Example 1 1.86 134.2 Comparative Example 2 3.15 227.6
[0134] Test conclusion:
[0135] According to the data in Table 3, the tensile strength of Examples 1 to 3 is between 5.18 MPa and 5.72 MPa, and the elongation at break is between 421.5% and 482.3%, indicating that the materials exhibit good mechanical strength and deformation adaptability.
[0136] Comparing the data of the comparative examples with those of Comparative Example 1, the tensile strength and elongation at break of Comparative Example 1 decreased to 1.86 MPa and 134.2%, respectively. Comparative Example 1 did not include dopamine for surface pretreatment of the inorganic fillers. This resulted in fewer active sites on the surfaces of the expandable graphite and hollow glass microspheres available for subsequent silane treatment, leading to a decrease in the interfacial bonding strength and interfacial continuity between the inorganic fillers and the polyurethane macromolecular network. Under tensile stress, interfacial slippage or debonding more easily occurs between the filler surface and the polymer matrix, forming stress concentration areas, which in turn leads to a decrease in the tensile strength and elongation at break of the material.
[0137] Comparing the data of the comparative examples with those of Comparative Example 2, the tensile strength of Comparative Example 2 is 3.15 MPa, and the elongation at break is 227.6%, which are all lower than those of Examples 1 to 3. Comparative Example 2 lacks zirconium acetylacetonate (IV) as an interface modifier. Although the filler surface is treated with silane containing epoxy groups, the interface reaction moderating effect is weakened, and the degree of interface reaction is reduced. The reduced bonding between the organic side chains on the filler surface and the polyurethane crosslinking structure leads to a decrease in the number of interfacial bonding points at the phase interface, and a decrease in the ability of the interfacial layer to transfer and disperse external stress during deformation.
[0138] Examples 1 to 3 utilize in-situ self-polymerization and coating of dopamine to provide more active sites on the filler surface, which is beneficial for the binding of silane coupling agents to the filler surface. Simultaneously, the interfacial regulation effect of metal complexes helps to enhance the degree of interfacial reaction, forming a more stable interfacial bonding layer between the inorganic filler and the organic resin. This interfacial bonding layer enables the material to maintain good strength and deformation capacity under external stress, thus demonstrating that interfacial treatment helps improve the mechanical properties of the cured coating.
[0139] Test Example 4:
[0140] Experimental steps:
[0141] (1) The isocyanate-modified polyurethane cyanide gas barrier materials prepared in Examples 1 to 3 and Comparative Example 5 were uniformly coated onto the surface of a polytetrafluoroethylene template with a corresponding thickness limit depth and smoothed. The ambient temperature was controlled at 25±2℃ and the relative humidity at 50±5%, and the material was allowed to cure for 14 days. The cured material was then peeled off from the template. For each test object, five strip samples with a length of 120mm, a width of 10mm, and a thickness of 4mm were cut out for the limiting oxygen index test, and three circular plate samples with a diameter of 150mm and a thickness of 5mm were cut out for the thermal conductivity test.
[0142] (2) The elongated sample is vertically fixed inside the transparent combustion chamber of the oxygen index analyzer. A mixture of oxygen and nitrogen is introduced, and the top of the elongated sample is ignited. The combustion of the elongated sample is observed. By adjusting the flow rate ratio of oxygen and nitrogen in the mixture, the percentage of the minimum oxygen volume required to maintain stable combustion of the elongated sample relative to the total volume of the mixture is recorded. Five elongated samples are tested in parallel for each test object, and the arithmetic mean is taken to calculate the limiting oxygen index of the test object.
[0143] (3) The circular plate sample is sandwiched between the hot and cold plates of the thermal conductivity meter. The surface temperature of the hot plate is set to 35°C and the surface temperature of the cold plate is set to 15°C. After the heat transfer reaches a steady state, the heat flux density through the circular plate sample and the actual temperature difference between the hot and cold plates are recorded. The heat flux density is multiplied by the thickness of the circular plate sample and then divided by the temperature difference between the hot and cold plates. Three circular plate samples are tested in parallel for each test object, and the arithmetic mean is taken to calculate the thermal conductivity of the test object.
[0144] The experimental results are shown in Table 4:
[0145] Table 4: Test Results of Flame Retardant and Thermal Insulation Properties of Cured Materials
[0146] object Limiting oxygen index (%) Thermal conductivity (W / (m·K)) Example 1 31.2 0.048 Example 2 32.5 0.045 Example 3 30.8 0.051 Comparative Example 5 27.6 0.064
[0147] Test conclusion:
[0148] According to the data in Table 4, the limiting oxygen index of Examples 1 to 3 is between 30.8% and 32.5%, and the thermal conductivity is between 0.045 W / (m·K) and 0.051 W / (m·K). The materials exhibit high flame retardant properties and low thermal conductivity.
[0149] Comparing the data of the comparative examples with those of Comparative Example 5, it can be seen that the limiting oxygen index of Comparative Example 5 decreased to 27.6%, and the thermal conductivity increased to 0.064 W / (m·K). Both the flame retardant and thermal insulation properties of the material showed a decline. Comparative Example 5 removed the bicycloxazolidine, and the material mainly relied on the direct reaction of free isocyanate groups with moisture in the air for curing. This curing path is more prone to the generation of carbon dioxide gas, causing pore defects to form in the cured material during the cross-linking process. On the one hand, these irregular pore defects reduce the continuity of the cured material, weaken the stable dispersion and closed-cell thermal insulation effect of hollow glass microspheres in the cured matrix, and may also form interconnected defect channels, collectively leading to an increase in thermal conductivity. On the other hand, these interconnected defect channels make it easier for oxygen and heat to transfer into the material during combustion, and the continuity of the carbonized layer formed by the thermal expansion of expandable graphite decreases when the cured matrix is insufficiently supported, thereby reducing the limiting oxygen index of the material.
[0150] Examples 1 to 3 employ a latent crosslinking agent in the curing reaction, reducing the risk of pore defects caused by carbon dioxide gas and helping to maintain the density of the polyurethane matrix. A relatively continuous and dense cured phase helps maintain the closed-cell thermal insulation effect of the hollow glass microspheres, while also providing support for the flame-retardant effect of expandable graphite. This facilitates the formation of a more continuous expanded carbon layer after heating, resulting in a lower thermal conductivity and a higher limiting oxygen index.
[0151] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. An isocyanate-modified polyurethane cyanide condensation barrier material, characterized in that, It is made from the following components in parts by weight: Isocyanate prepolymer mixture: 140-150 parts; Modified composite powder filler: 42.05–59.8 parts; Molecular sieve activated powder: 3-5 parts; Bicycloxazolidine: 8–12 parts; The modified composite powder filler is made from raw materials comprising the following parts by weight: Expandable graphite: 30-40 parts; Hollow glass microspheres: 10-15 parts; Dopamine hydrochloride: 0.2–0.8 parts; γ-glycidyl etheroxypropyltrimethoxysilane: 1.5–2.5 parts; Zirconium acetylacetonate (IV): 0.05–0.30 parts; Triethyl orthoformate: 0.3–1.2 parts.
2. The isocyanate-modified polyurethane cyanide-coated gas barrier material according to claim 1, characterized in that, The components comprise the following parts by weight: the isocyanate prepolymer mixture: 145 parts; the modified composite powder filler: 50.45 parts; the molecular sieve activated powder: 4 parts; and the bicyclooxazolidine: 10 parts.
3. The isocyanate-modified polyurethane cyanide-coated gas barrier material according to claim 1, characterized in that, The isocyanate prepolymer mixture is made from raw materials comprising the following parts by weight: Polyphenyl polymethylene polyisocyanate: 100 parts; Polytetramethylene ether glycol: 40-50 parts.
4. The isocyanate-modified polyurethane cyanide-coated gas barrier material according to claim 1, characterized in that, The expansion ratio of the expandable graphite is 150 mL / g to 250 mL / g.
5. A method for preparing an isocyanate-modified polyurethane cyanide condensation barrier material as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Add the modified composite powder filler, isocyanate prepolymer mixture and molecular sieve activated powder into a disperser and disperse at 600 r / min to 1000 r / min for 15 to 25 minutes to obtain the composite initial mixture slurry. S2. Control the temperature of the composite initial mixture to drop to 15℃~20℃, turn on the vacuum pump to evacuate to -0.095MPa~-0.098MPa, disperse at 2000r / min~3000r / min under constant temperature and vacuum conditions, inject bicycloxazolidine into the composite initial mixture, maintain dispersion and continue stirring for 20~40 minutes to obtain a degassing and sealing mixture; then fill the degassing and sealing mixture with dry nitrogen to release the vacuum, and package and seal to obtain the isocyanate modified polyurethane cyanopolymer gas barrier material.
6. The method for preparing the isocyanate-modified polyurethane cyanide-coated gas barrier material according to claim 5, characterized in that, Prior to step S1, the preparation steps of the isocyanate prepolymer mixture include: Polyphenyl polymethylene polyisocyanate was added to a nitrogen-protected reactor, and the temperature was raised to 65°C to 70°C with stirring. Polytetramethylene ether glycol was added dropwise to the reactor at a uniform rate over 30 to 60 minutes. After the addition was completed, the temperature of the reactor was raised to 80°C to 85°C, and the reaction was stirred continuously for 2 to 3 hours. The mixture was then cooled to obtain the isocyanate prepolymer mixture.
7. The method for preparing the isocyanate-modified polyurethane cyanide-coated gas barrier material according to claim 5, characterized in that, Prior to step S1, the preparation steps of the modified composite powder filler include: (1) Expandable graphite and hollow glass microspheres are added to a mixed solvent prepared with anhydrous ethanol and water and stirred to obtain a suspension. The pH value of the suspension is adjusted, and dopamine hydrochloride is added and stirred to obtain a primary activation mixture. The primary activation mixture is subjected to pressure filtration to separate and retain solid substances to obtain a primary filter cake. The primary filter cake is washed with anhydrous ethanol and then vacuum dried to obtain a pre-activated packing material. (2) The pre-activated packing is transferred into a mixing tank, and γ-glycidyl ether oxypropyltrimethoxysilane is sprayed in and heated and stirred to obtain silane-treated packing; then the temperature is lowered and zirconium acetylacetonate (IV) is added under nitrogen protection and stirring is continued to obtain pre-regulated modified packing. (3) Triethyl orthoformate is sprayed into the mixing vessel and stirred in a closed manner with the pre-regulated modified filler to obtain the dehydrated reaction material; then vacuum dehydration is performed, and after the vacuum is completed, dry nitrogen is introduced to release the vacuum and the temperature is lowered to obtain the modified composite powder filler.
8. The method for preparing the isocyanate-modified polyurethane cyanide condensation barrier material according to claim 7, characterized in that, In step (1), the pH of the suspension is adjusted to 8.0-8.5 by adding tris(hydroxymethyl)aminomethane aqueous solution; after adding the dopamine hydrochloride, the temperature is controlled at 25℃-40℃ and stirred continuously for 1-3 hours; the vacuum drying conditions are: the temperature is controlled at 100℃-120℃ and dried until the moisture content is not greater than 0.05%.
9. The method for preparing the isocyanate-modified polyurethane cyanide-coated gas barrier material according to claim 7, characterized in that, In step (2), the temperature is controlled at 80℃~90℃ during heating and stirring and stirring is maintained for 1~1.5 hours; the cooling is to cool down to 60℃~70℃, add zirconium acetylacetonate (IV) and continue stirring for 20~40 minutes; In step (3), after the triethyl orthoformate is added by spray, the conditions for the closed stirring are: the temperature is controlled at 60℃~70℃, and the stirring is carried out for 15~20 minutes; the conditions for the vacuum suction dehydration are: the vacuum degree is drawn to -0.090MPa~-0.098MPa, and the vacuum state is maintained at 60℃~70℃ for 30~45 minutes.
Citation Information
Patent Citations
Self-skinning modified polyurethane thermocuring sealant composition and preparation method thereof
CN111574951A
Isocyanate composition, polyurethane adhesive and application thereof
CN117003984A